Adsorption of Thiophenic Compounds from n-Hexane Using Activated Carbon Adsorbent - Kareem, Yousra Saber (Nahrain University College of Engineering Journal, 2015)
The aim of this work is to study the adsorption of thiophenic compounds (thiophene and benzo thiophene) on activated carbon by studying the effects of various important variables such as height of the bed (4, 6, and 8 cm) , inlet sulfur concentration (50, 75, 90, and 100 PPM), and flow rate of the liquid n-hexane feed (4, 13, and 20 ml/min.).The activated carbon has very high affinity for the sulfur compounds in the order benzo thiophene > thiophene. In Fixed bed experiments the concentration of sulfur out (Co) with time decreases with increasing of bed height, flow rate, and the initial concentration of sulfur compounds. The maximum percent removal of thiophene was reached to 70% at initial concentration 50PPM at bed height 6 cm and feed flow rate of 4 ml/min., while the maximum percent removal of benzo thiophene was reached to 73% at initial concentration 75PPM at bed height 4 cm and feed flow rate of 4 ml/min.